SYNTACTIC FEATURES OF SIMPLE TONGUE TWISTERS - Xamzayev Otakhon Erkinovich, (World Scientific Research Journal, 2025)
Abstract: This article is devoted to the study of the syntactic structure of simple sentences in the Uzbek language. It analyzes the classification of quick utterances according to sentence types, their structure and grammatical features. Throughout the article, various examples are presented, through which the logical and aesthetic aspects of fast sayings are revealed.